2016
DOI: 10.1016/j.ynstr.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced increases in progesterone and cortisol in naturally cycling women

Abstract: Studies with animals of both sexes show that the adrenal glands release progesterone in addition to cortisol in response to stress. However, little is known about the progesterone response to stress in naturally cycling women. We investigated the effect of stress on estradiol, progesterone, and cortisol levels in women during the follicular phase of the menstrual cycle. We found that physical stress (the cold pressor test) had no effect on estradiol levels, but increased progesterone and cortisol. We also foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 44 publications
4
54
0
4
Order By: Relevance
“…In addition, a higher concentration of progesterone in the pregnant HS cows supported our findings because there is a positive correlation between progesterone concentration and rectal temperature during pregnancy [40]. Progesterone secreted from corpus luteum/placenta during pregnancy, and stress-responded progesterone from adrenal glands may be responsible for the increased level [41, 42]. Surprisingly, however, we did not find downregulation of progesterone levels caused by the dysfunction of the corpus luteum during long-term HS.…”
Section: Discussionsupporting
confidence: 70%
“…In addition, a higher concentration of progesterone in the pregnant HS cows supported our findings because there is a positive correlation between progesterone concentration and rectal temperature during pregnancy [40]. Progesterone secreted from corpus luteum/placenta during pregnancy, and stress-responded progesterone from adrenal glands may be responsible for the increased level [41, 42]. Surprisingly, however, we did not find downregulation of progesterone levels caused by the dysfunction of the corpus luteum during long-term HS.…”
Section: Discussionsupporting
confidence: 70%
“…An important consideration in human research on the P/E ratio, and PTSD research in particular, is the influence of stress on progesterone and estradiol levels. In addition to cortisol, the adrenal glands secrete progesterone as part of the stress response and higher progesterone levels have been associated with higher levels of available cortisol (Deis, Leguizamon, & Jahn, 1989;Herrera, Nielsen, & Mather, 2016;Roca et al, 2003;Wirth, Meier, Fredrickson, & Schultheiss, 2007). Thus, during high progesterone phases of the menstrual cycle, the contribution of stress may further increase progesterone levels and inflate the P/E ratio.…”
Section: Recommendations For Future Human Research On the P/e Ratiomentioning
confidence: 99%
“…Roca et al () have demonstrated that progesterone administration increased HPA‐axis response to exercise. Herrera, Nielsen, and Mather () found that higher baseline progesterone levels during the low progesterone follicular phase were associated with higher cortisol in response to stress after the cold pressor test. Inconsistency in results may derive from differences between ovarian progesterone and adrenal progesterone.…”
Section: Discussionmentioning
confidence: 99%
“…While the adrenals are the main source of progesterone in males, both ovaries and the adrenal are the source of progesterone in women (Wirth, Meier, Fredrickson, & Schultheiss, 2007). An association between ovarian and adrenal progesterone across the menstrual cycle in women was also demonstrated (Herrera et al, 2016). Future studies should further investigate the role of progesterone in modulating the HPA-axis reactivity to stress in men and women across the menstrual cycle.…”
Section: Reschkementioning
confidence: 90%